Microvideo Neurofeedback-Oriented Approach in Science Subjects for Grade IV Elementary Students - Gunawan, I Kadek arya; Adrianus I Wayan Ilia Yuda Sukmana; Alexander Hamonangan Simamora (Jurnal Media dan Teknologi Pendidikan, 2025)
The use of innovative learning media is crucial in creating an engaging, interactive, and effective learning process. There is a growing need for media that can enhance students' active engagement through the integration of neurofeedback elements. This study aims to develop neurofeedback-oriented animated micro-videos for the Science and Social Studies (IPAS) subject in fourth-grade elementary school. The method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of three experts (in content, media, and instructional design), three students for the individual trial, six students for the small group trial, and 28 fourth-grade students in the field trial through pre-test and post-test procedures. Data were collected through interviews, questionnaires, and expert validations. The validation results showed that the material and media aspects received a feasibility score of 98%, while the instructional design component received 95%, all categorized as "very good". Student responses in both the individual and small group trials were 100% positive. The study concludes that the neurofeedback-oriented animated micro-video media is feasible to be implemented to support IPAS learning in a more effective and interactive manner. The implications of this study suggest that the integration of neurofeedback-based technology in learning media holds significant potential for improving the quality of instruction and supporting instructional differentiation across various learning contexts.